The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/bf03346748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metabolic syndrome and its components on prostate cancer risk: Meta-analysis

Abstract: Metabolic syndrome is weakly and non significantly associated with prostate cancer risk, but associations vary with geography. Among single components of the syndrome, hypertension and higher waist circumference are significantly associated with increased risk of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
75
4
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 51 publications
(63 reference statements)
10
75
4
9
Order By: Relevance
“…Some reviews that have linked obesity with prostate cancer have indicated that obesity may not necessarily increase the risk of prostate cancer, but may promote it once established. [9] A similar finding was documented in a study among healthy Koreans that showed higher waist circumference and fasting plasma glucose level were significantly associated with lower PSA (low risk for PCa) but not with MetS, [10] while in another meta analysis by Esposito et al, [11] found higher waist circumference to be significantly associated with increased levels of PSA. Previous studies demonstrated that men with type 2 diabetes mellitus consistently had significantly lower serum prostate-specific antigen levels than healthy men.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Some reviews that have linked obesity with prostate cancer have indicated that obesity may not necessarily increase the risk of prostate cancer, but may promote it once established. [9] A similar finding was documented in a study among healthy Koreans that showed higher waist circumference and fasting plasma glucose level were significantly associated with lower PSA (low risk for PCa) but not with MetS, [10] while in another meta analysis by Esposito et al, [11] found higher waist circumference to be significantly associated with increased levels of PSA. Previous studies demonstrated that men with type 2 diabetes mellitus consistently had significantly lower serum prostate-specific antigen levels than healthy men.…”
Section: Introductionsupporting
confidence: 68%
“…Most of the reviews and meta analysis are as varied as always on the complicity of metabolic syndrome in prostate cancer pathogenesis. A meta analysis by Esposito K. et al, [11] showed that metabolic syndrome is weakly and non significantly associated with prostate cancer and this varies with geography, race and/or ethnicity while Gacci M. et al, [7] and Rhee H. et al, [8] in a more recent meta analysis revealed that metabolic syndrome may not be involved directly in the pathogenesis of prostate cancer rather it is associated with severity of the tumour including its aggressiveness, worse outcome and biochemical recurrence on the background hormones dysregulation. Although the relationship between metabolic syndrome and prostate cancer is inconclusive and more often than not confusing, the individual components of metabolic syndrome maintain a Section: Medicine rather definitive heterogeneous relationship with serum total PSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic syndrome has been linked with an increased risk of PCa [5], but there is insufficient evidence to recommend lifestyle changes or a modified diet to lower this risk. In hypogonadal men, testosterone therapy is not associated with an increased PCa risk [6].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome is linked with prostate cancer risk and varies with geography (Esposito et al, 2013). The pervasiveness of metabolic syndrome is rising worldwide and allied with an augmented risk of the assertiveness and succession of prostate cancer (Xiang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%